2013
DOI: 10.1080/09084282.2012.747959
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Select Dimensions of Patients' Emotional Functioning at Different Time Periods After Stroke

Abstract: A person's self-evaluation influences purposeful activity undertaken in the situation of illness. It is observed in neurological patients that limited self-awareness disturbs rehabilitation. The goal of the study was to investigate select dimensions of emotional state, the relationship between anxiety and emotional state, and the level of insight into emotional state in patients at different time periods after cerebral vascular accidents (CVAs). Sixty-five patients with short (n = 36) or long (n = 29) time per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In previous studies, an increased risk of depression 13–15 and anxiety 11 was noted after diagnosis of stroke, 11,13–15 hypertension, 17 coronary artery disease 31 and atrial fibrillation. 32 Such risk elevations has been suggested to be persistent over time, 10,33,34 and, in parallel with our findings, associated with compromised survival. 8,35,36 However, the evidence from prospective cohort studies with a long and complete follow-up as well as with a thorough control of confounding factors and comorbid conditions has, up to this point, been limited.…”
Section: Discussionsupporting
confidence: 89%
“…In previous studies, an increased risk of depression 13–15 and anxiety 11 was noted after diagnosis of stroke, 11,13–15 hypertension, 17 coronary artery disease 31 and atrial fibrillation. 32 Such risk elevations has been suggested to be persistent over time, 10,33,34 and, in parallel with our findings, associated with compromised survival. 8,35,36 However, the evidence from prospective cohort studies with a long and complete follow-up as well as with a thorough control of confounding factors and comorbid conditions has, up to this point, been limited.…”
Section: Discussionsupporting
confidence: 89%
“…The mismatches (over-and under-estimations) between observational and self-reported outcome measures could be attributed to different causes. Underestimations of self-reported capacity in the first 3 months may be associated with a more pronounced disturbed self-awareness (20), a limited insight into one's own functioning (19), more negativity-prone thoughts, and lack of information about the rehabilitation phase. Another possibility is that the improved, but affected, upper limb capacity is insufficiently used in daily activities, so that functional recovery is not fully experienced.…”
Section: Proportion Of Matches Between Observational and Self-reporte...mentioning
confidence: 99%
“…For the first aim, it was hypothesized that there would be a higher proportion of matches at 3-6 months than at 0-3 months post-stroke, because patients gradually learn to deal better with and gain more experience of real-world limitations, with a better understanding of their own capabilities (19)(20)(21). For the second aim, it was hypothesized that more patients would overestimate ("optimistic"') than underestimate ("pessimistic") their self-reported capacity at 0-3 months post-stroke than at 3-6 months post-stroke, because spontaneous neurological and functional recovery occurs within the first 3 months post-stroke.…”
mentioning
confidence: 99%
“…According to Zawadzka and Domańska (2014) and to Kim (2016), the most frequent emotional changes after stroke include depression. In this line of thought, Hackett and Pickles (2014) demonstrated that during the first-year after stroke, between 31 and 33% of patients had depression, and between the first and fifth year after stroke, the proportion of patients with depression was 25%.…”
Section: Introductionmentioning
confidence: 99%
“…The studies comparing the prevalence of depression after 12 months (chronic period) are scarcer. Recently, Zawadzka and Domańska (2014) have shown that there is a decrease in symptomatology of depression after the first year; however, it may increase again after two or three years. On the other hand, Liman et al (2012) found similar prevalence of depression for the chronic period (after three and five years: 10.0 and 9.6% respectively) and for the medium duration period (at 12 months: 11.4%).…”
Section: Introductionmentioning
confidence: 99%